Investigating critical resource determinants of start-ups: An empirical study of the MENA region - Abdulaziz Abdulmohsen Alfalih (Cogent Economics & Finance, 2019)
Purpose: By drawing upon the resource-based view theory, this study investigates the critical resource determinants of start-up companies in the Middle East and North Africa (MENA) region in order to encourage the development of entrepreneurship in the region. Design/methodology/approach: A quantitative approach based on multiple linear hierarchical regression analysis was used. Three sets of data were employed. Firstly, the study used the World Bank's Doing Business Report which investigated the ease of starting businesses, access to electricity and access to credit across the 23 MENA countries. Secondly, the study also used the human capital index from the Global Entrepreneurship Index as one of the predictor variables of start-ups. Finally, three specific data sets, namely population, Foreign Direct Investment (FDI) and Gross Domestic Product of the 23 MENA countries were used as control variables due to their importance as determinants of entrepreneurship orientation. Findings: The results of this study indicate that access to two critical resources, namely electricity and credit, have greatly contributed to the formation of start-ups in the MENA region. However, the current level of human capital in the region does not support entrepreneurial activity, hence its inability to support entrepreneurs in the venture creation process. There is a need to augment entrepreneurship education across the region, as well as the provision of entrepreneurial skill development to current and potential entrepreneurs. Research limitations/implications: Firstly, the study depended heavily on secondary data to examine the determinants of start-ups in the MENA region. Even though the sources of these data are credible, it is impossible to determine any anomalies in the original data. Secondly, the model used in this study is parsimonious in the sense that many more predictor variables could have been explored in understanding the determinants of start-ups in the region. Future research could therefore investigate other factors, such as technology, property rights, the legal system and other important factors in the entrepreneurial ecosystem of the MENA region. Originality/value: Start-ups are a major source of new employment in a country. However, it is essential to understand the various factors which foster their survival and growth. Even though similar studies have been conducted in various settings, this is one of the few studies which have focused on empirical investigation into the resource determinants of start-ups in the MENA region. The MENA region is noted for its access to abundant oil reserves and other resources. However, this has not culminated in the emergence of successful start-ups. This is what has necessitated this study; to investigate the factors that are responsible for start-up growth in the region. The uniqueness of this study is that it is one of the few studies which have used a three-factor construct in investigating the drivers of start-ups in the MNEA region. This study adopts an exhaustive approach with different variables in different levels of analysis which can provide extra information for further comparative study.
Keywords: 330; credit; electricity; human capital; MENA; Middle East; resource-based view theory